Analysis on the success factors in determining sales value of taxable object - Agustinus Imam Saputra; Irwan Taufiq Ritonga (Jurnal Akuntansi dan Auditing Indonesia, 2020)
This study aims to examine the contradiction in determining Sales Value of Taxable Object (SVTO) in accordance with fair market price in Bantul Regency and Yogyakarta City. This study elaborates the success factors of Yogyakarta City in determining SVTO which approaches the market price. The study used descriptive qualitative method with a case study design. The research data were obtained using in-depth interview and document review. The theoretical basis used was the pressure of isomorphism in institutional theory (DiMaggio & Powell, 1983). The preliminary research was conducted at five Primary Tax Offices of Directorate General of Taxes (DGT) Regional Office in Daerah Istimewa Yogyakarta Province. The respondents of this study were employees of the Revenue and Regional Asset Management Office (BPKAD) Yogyakarta and Financial and Regional Assets Office (BKAD) Bantul. The results show that SVTO determination in Bantul is influenced by normative isomorphism pressure because Bantul follows the group norms of surrounding local governments. On the other hand, SVTO determination in Yogyakarta is influenced by coercive pressure because Yogyakarta tends to follow the laws and regulations. The essential lessons from Yogyakarta City are the readiness of regulations, use of reliable data, incentive provision, increase in the untaxable value of the sales value of taxable object, extensive socialization, and recruitment of appraisers. Bantul should refer to the Laws and Yogyakarta City, as the best practices in determining SVTO. This research can be a preliminary of further research in a broader area or on nationwide level.